Impact of long-term exposure to ambient ozone on lung function over a course of 20 years (The ECRHS study): a prospective cohort study in adultsResearch in context - Tianyu Zhao; Iana Markevych; Elaine Fuertes; Kees de Hoogh; Simone Accordini; Anne Boudier; Lidia Casas; Bertil Forsberg; Judith Garcia Aymerich; Marco Gnesi; Mathias Holm; Christer Janson; et al. (Elsevier, 2023)
Summary: Background: While the adverse effects of short-term ambient ozone exposure on lung function are well-documented, the impact of long-term exposure remains poorly understood, especially in adults. Methods: We aimed to investigate the association between long-term ozone exposure and lung function decline. The 3014 participants were drawn from 17 centers across eight countries, all of which were from the European Community Respiratory Health Survey (ECRHS). Spirometry was conducted to measure pre-bronchodilation forced expiratory volume in 1 s (FEV1) and forced vital capacity (FVC) at approximately 35, 44, and 55 years of age. We assigned annual mean values of daily maximum running 8-h average ozone concentrations to individual residential addresses. Adjustments were made for PM2.5, NO2, and greenness. To capture the ozone-related change in spirometric parameters, our linear mixed effects regression models included an interaction term between long-term ozone exposure and age. Findings: Mean ambient ozone concentrations were approximately 65 μg/m³. A one interquartile range increase of 7 μg/m³ in ozone was associated with a faster decline in FEV1 of −2.08 mL/year (95% confidence interval: −2.79, −1.36) and in FVC of −2.86 mL/year (−3.73, −1.99) mL/year over the study period. Associations were robust after adjusting for PM2.5, NO2, and greenness. The associations were more pronounced in residents of northern Europe and individuals who were older at baseline. No consistent associations were detected with the FEV1/FVC ratio. Interpretation: Long-term exposure to elevated ambient ozone concentrations was associated with a faster decline of spirometric lung function among middle-aged European adults over a 20-year period. Funding: German Research Foundation.